Effectiveness and safety of minimally invasive Ivor Lewis and McKeown oesophagectomy in Chinese patients with stage IA–IIIB oesophageal squamous cell cancer: a multicentre, non-interventional and observational study. (14th April 2020) - Zhang, Tong; Hou, Xiaobin; Li, Yin; Fu, Xiangning; Liu, Lunxu; Xu, Lin; Liu, Yang
Abstract: OBJECTIVES: To compare the long-term overall survival and outcomes of patients with oesophageal squamous cell cancer treated with minimally invasive McKeown or Ivor Lewis oesophagectomy. METHODS: A multicentre, non-interventional, retrospective, observational study was performed in oesophageal squamous cell cancer patients pathologically confirmed with stage IA–IIIB middle or lower thoracic tumours who underwent minimally invasive oesophagectomy between 1 January 2010 and 30 June 2017 in 7 hospitals in China. Cox proportional hazards models assessed factors associated with overall survival and disease recurrence. The primary outcome was overall survival and cancer recurrence; the secondary outcomes included number of lymph nodes resected, 30-day mortality and postoperative complications. RESULTS: A total of 1540 patients were included (950 McKeown, 590 Ivor Lewis). The mean age was 61.6 years, and 1204 were male. The mean number of lymph nodes removed during the McKeown procedure was 21.2 ± 11.4 compared with 14.8 ± 8.9 in Ivor Lewis patients ( P < 0.001). The 5-year overall survival rates were 67.9% (McKeown) and 55.0% (Ivor Lewis). McKeown oesophagectomy was associated with improved overall survival (Ivor Lewis versus McKeown hazard ratio 1.36, 95% confidence interval 1.11–1.66; P = 0.003), particularly in patients with stage T3 tumours (middle thoracic oesophagus). However, postoperative complications occurred more frequently following McKeown oesophagectomy (42.2% vs 17.6% Ivor Lewis; P < 0.001). CONCLUSIONS: Minimally invasive McKeown oesophagectomy was associated with improved overall survival and a decreased risk of disease recurrence, while Ivor Lewis patients had fewer postoperative complications. McKeown oesophagectomy may represent the optimal technique for patients with stage T3 tumours. Clinical trial registration: clinicaltrial.gov: NCT03428074